أثر تدريس وحدة مطورة متكاملة في العلوم على تنمية التحصيل والاتجاه لدى طلاب المرحلة الابتدائية بالمملكة العربية السعودية - غتم، محمد بن أحمد (Kulliyyah of Education, International Islamic University Malaysia, 2017)
This study aims to identify the effect of teaching a developed integrated unit in science in enhancing sixth grade students' achievement and their attitude towards science in Al-Ahsa governorate, in Kingdom of Saudi Arabia. To achieve the study objectives, the quasi-experimental research design was utilized. The researcher used a developed unit based on integration between science and religious culture, a teacher guide to teach the developed integrated unit, an achievement test, and a scale to measure students' attitude towards science. The researcher prepared a list of criteria and indicators to develop a study unit based on the integration between science, and religious culture; it included (38) indicators, classified under four criteria in terms of aims, content, activities and evaluation. The study sample consisted of (63) sixth grade students from Salah Uddin elementary school, divided into two groups; a control group with (30) students and an experimental group with (33) students. The descriptive statistics (i.e. Means and Standard deviations), Pearson product moment Correlation Coefficient, Cronbach's alpha Coefficient, discrimination index, difficulty index, t-test and Cohen's d were used in the data analysis. The study results showed that there was a statistically significant difference in students' mean scores in the post achievement test between the students in the experimental group, (who studied the developed unit based on integration between science and religious culture) and students in the control group (who studied the unit in the textbook) in favor of the experimental group; with a large effect size (Cohen's d = 1.3), Whereas, there was no statistically significant difference in the mean scores in students' attitude for both groups. In essence, the results showed a clear positive impact of the developed integrated unit on the achievement of students in the experimental group compared to their peers in the control group. However, there was no effect for the integrated unit on the students' attitude towards science. This might be due to the short duration of the research experiment. The study recommends that it is necessary to include selected holly Quranic verses and Prophetic Hadiths with their scientific explanation in the science subjects offered in the primary schools. It also recommends constructing interrelated curricula, which will contribute to the development of scientific concepts among the students.